Scrobipalpa antoniovivesi Huemer, sp. n., a remarkable new species from Spain (Lepidoptera: Gelechiidae) - P. Huemer (SHILAP)
Scrobipalpa antoniovivesi Huemer, sp. n., a new species of the tribe Gnorimoschemini, family Gelechiidae, is described from Spain (Huesca). The adult and male genitalia are figured, whereas the female sex remains unknown. The nearest species S. dorsolutea Huemer & Karsholt, 2010 is only known from the southern Ural Mountains. (Russian Federation). However, the new species differs both morphologically and in the DNA barcode from this taxon and all other known representatives of the genus.